2006
DOI: 10.1021/bi052062d
|View full text |Cite
|
Sign up to set email alerts
|

Solution Structures of Spinach Acyl Carrier Protein with Decanoate and Stearate,

Abstract: Acyl carrier protein (ACP) is a cofactor in a variety of biosynthetic pathways, including fatty acid metabolism. Thus it is of interest to determine structures of physiologically relevant ACP-fatty acid complexes. We report here the NMR solution structures of spinach ACP with decanoate (10:0-ACP) and stearate (18:0-ACP) attached to the 4′ phosphopantetheine prosthetic group. The protein in the fatty acid complexes adopts a single conformer, unlike apo-and holo-ACP, which interconvert in solution between two ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
144
1
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(156 citation statements)
references
References 46 publications
7
144
1
4
Order By: Relevance
“…harveyi ACP° [23].°This°stabilization°occurs°as°the acyl chain is enclosed within the relatively hydrophobic interior of the three parallel ␣-helices of folded ACP, as indicated°by°both°NMR° [21]°and°X-ray°crystallography [20].°As°shown°in°Figure°5a,°the°CSD°of°myristoyl-ACP was°very°similar°to°that°of°apo-rACP°(Figure°2a)°at neutral pH (average net charge 7.6), although only the former would actually be in a folded helical conformation°in°solution°under°these°conditions° (Figure°1d).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…harveyi ACP° [23].°This°stabilization°occurs°as°the acyl chain is enclosed within the relatively hydrophobic interior of the three parallel ␣-helices of folded ACP, as indicated°by°both°NMR° [21]°and°X-ray°crystallography [20].°As°shown°in°Figure°5a,°the°CSD°of°myristoyl-ACP was°very°similar°to°that°of°apo-rACP°(Figure°2a)°at neutral pH (average net charge 7.6), although only the former would actually be in a folded helical conformation°in°solution°under°these°conditions° (Figure°1d).…”
Section: Resultsmentioning
confidence: 93%
“…The NMR solution structure of several ACPs reveal a highly conserved folded conformation consisting of three parallel ␣-helices; in acyl-ACP, these helices enclose a fatty acyl group that is covalently attached to the 4=-phosphopantetheine prosthetic group [20,21]. Based on circular dichroism (CD) and hydrodynamic approaches, ACP from some bacterial species such as Vibrio harveyi is largely unfolded in solution at neutral pH, and its folded conformation can be stabilized by either fatty acylation or divalent cation binding to the acidic Helix II [22][23][24].…”
mentioning
confidence: 99%
“…Several structures of type II ACPs with bound acyl chains of different length showed that the insoluble fatty acid was buried deep within a hydrophobic pocket of the ACP, which might represent a transport form for substrate shuttling between the individual enzymes (Roujeinikova et al 2007 ;Zornetzer et al 2006). Based on these observations, Leibundgut et al proposed a switchblade-like mechanism, in which the acyl chain remains buried within the fungal ACP during inter-domain-shuttling in a similar manner as observed in type II FAS, whereas it is flipped out into the hydrophobic reaction pockets for catalysis .…”
Section: Active Sites Linkers and Substrate Shuttling In Fungal Fasmentioning
confidence: 99%
“…The coding regions of the C-and N-terminal splicing domains of the Ssp GyrB intein were amplified from pDSG 3 with primer pairs IC-for/IC-rev and IN-for/INHIS-rev, respectively; the products were fused by anneal-extension PCR and subsequently amplified using primers IC-for/INHIS-rev. The complete product was cloned into pT (a derivative of the pTWIN1 vector from New England Biolabs) 4 using SacI and PstI, creating pTI C (NS)I N H. The coding regions of the V. harveyi ACP L46W and F50A mutants were amplified from pGEX-L46W (15) and pGEX-F50A (20), respectively, using primers ACP-for/ACP-rev and cloned into pTI C (NS)I N H using NheI and SapI, resulting in pTCYC-L46W and pTCYC-F50A.…”
Section: Methodsmentioning
confidence: 99%
“…Over two dozen nuclear magnetic resonance (NMR) and x-ray crystal structures have revealed a conserved "ACP fold" consisting of a four-helix bundle (1). Fatty acids covalently attached to the phosphopantetheine prosthetic group at the N-terminal end of helix II are enclosed within the hydrophobic interior of this bundle, interacting predominantly with residues on helices II-IV (2)(3)(4)(5). Further computational (6,7), crystallographic (8,9), and mutagenic (10 -13) analyses have implicated the acidic central helix II as a "recognition helix" for interaction with most of the ACP enzyme partners.…”
Section: Bacterial Acyl Carrier Protein (Acp)mentioning
confidence: 99%